ASSESSMENT OF SOCIAL AND ECONOMIC DAMAGE ASSOCIATED WITH MORTALITY FROM RESPIRATORY CANCER IN THE TOMSK REGION (2005–2016) - L. D. Zhuikova; E. L. Choynzonov; O. A. Ananina; A. S. Zhuikova; T. V. Polychuk (Сибирский онкологический журнал, 2021)
Introduction. A significant component in the system analysis of anti-cancer activities is the assessment of the impact of mortality on life expectancy, which indicates the social and economic situation in the region.Material and methods. The economic damage caused by laryngeal and lung cancer mortality in the Tomsk region for the period 2005–2016 was analyzed using the database of the regional cancer registry and local agency of federal state statistics service of the tomsk region.Results. The loss of the male working population ranged from 106.0 (2012–2013) to 161.5 (2008–2009) person/years of lifetime from larynx cancer and from 1058.5 (2013–2014) to 1576.3 (2006–2007) person/years of lifetime from lung cancer. The female working population lost up to 34.0 (2013–2014) person/years of lifetime due to mortality from larynx cancer and from 1445.3 (2005–2006) to 2553.9 (2015–2016) person/years of lifetime from lung cancer. The average number of undelivered years in working age due to the premature death of one man averaged 6.1 ± 2.0 years from larynx cancer and 11.1 ± 1.3 from lung cancer, one woman averaged 4.6 ± 0.9 years from larynx cancer and 6.2 ± 0.3 years from lung cancer. Economic losses associated with mortality from cancer of the respiratory system amounted to 2.251.97 million rubles: 202.07 million rubles from laryngeal cancer and 2.049.90 million rubles from lung cancer.Conclusion. The quantitative analysis of social and economic losses associated with mortality from cancer of the respiratory system enables the regional health authorities to develop and implement anti-cancer interventions to maximize the use of funds for the prevention, treatment and rehabilitation of cancer patients.